Financial market reform – A new driver for China's economic growth? - Yu-Fu Chen; Michael Funke; Kunyu Tao (Bank of Finland, Institute for Economies in Transition (BOFIT), 2015)
This paper analyses the financial distortions – growth nexus in China using a tractable general equilibrium modelling approach in which heterogeneous private and state-owned firms interact. The focal points of the model are financial frictions and reallocations of factors of production across firms. The calibrated version of the model elicits the important message that the adoption of a comprehensive financial market reform package abolishing financial distortions will lead to substantial output gains. Thus, structural policies leading to more efficient allocation of factors of production will remain a key policy challenge in China in the years to come. Publication
URN:NBN:fi:bof-201502231049
Keywords: C68; G10; G38; O10; 330; financial distortions; financial liberalisation; general equilibrium model; China